2021
DOI: 10.1007/s10549-021-06390-6
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of receptor expression discordance between primary and recurrent breast cancers: a meta-analysis

Abstract: Purpose This meta-analysis aimed to investigate whether receptor (estrogen receptor [ER], progesterone receptor [PR], and human epidermal growth factor receptor 2 [HER2]) discordances between primary and recurrent breast cancers affect patients’ survival. Methods Search terms contained ER, PR, and HER2 status details in both primary and recurrent tumors (local recurrence or distant metastasis) in addition to survival outcome data (overall survival [OS] or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Changes in the status of ER, PR, and HER2 status between CNB and excision specimens, between primary and metastatic tumours, and following neoadjuvant therapy have been the subject of many reviews and meta-analyses [91][92][93] including a review in this issue of the journal. Loss of ER or PR in recurrent tumours is associated with shorter outcome compared with receptor-positive concordance.…”
Section: Modification Of Er Pr and Her2 Status During Bc Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in the status of ER, PR, and HER2 status between CNB and excision specimens, between primary and metastatic tumours, and following neoadjuvant therapy have been the subject of many reviews and meta-analyses [91][92][93] including a review in this issue of the journal. Loss of ER or PR in recurrent tumours is associated with shorter outcome compared with receptor-positive concordance.…”
Section: Modification Of Er Pr and Her2 Status During Bc Evolutionmentioning
confidence: 99%
“…Loss of ER or PR in recurrent tumours is associated with shorter outcome compared with receptor-positive concordance. Contrasting this, gain of ER is associated with longer survival compared with receptor-negative concordance [93]. Despite the clinical evidence of the impact of the receptor discordance and the high rate of phenotypic drift reported in some studies, we advise investigating such discordant cases to exclude false-positive or -negative results.…”
Section: Modification Of Er Pr and Her2 Status During Bc Evolutionmentioning
confidence: 99%
“…In our study, there were 36 patients (11.8%) with unknown receptor status of ILRR, and we analyzed these patients using the receptor status of the primary tumor as a proxy. Receptor status of primary tumors and recurrent tumors are known to be discordant in a certain percentage of patients [ 39 ]. In our study ER, PR, and HER2 statuses were found to be discordant in 12.5%, 25.9%, and 7.7% of patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these challenges, it is recommended that biomarker assessment on metastatic BC lesions is critical for the clinical care of patients with advanced BC. ASCO clinical practice guidelines recommend that all BC biomarkers be reassessed in recurrent or metastatic lesions, as biomarker status can change with disease progression and have therapeutic implications 39,40 . This specific issue of biomarker instability with disease progression may be especially relevant to BC with low levels of HER2 expression.…”
Section: Continued Diagnostic Challenges and Unresolved Questions In ...mentioning
confidence: 99%